Phân tích đa thức thành nhân tử
a4 + b4 + 4a2b2 - 3ab ( a2 + b2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a^4+b^4+c^4-2a^2b^2-2b^2c^2-2a^2c^2=\left(a^4-2a^2b^2+b^4\right)+2\left(a^2-b^2\right)c^2+c^4-4a^2c^2=\left(a^2-b^2+c^2\right)^2-\left(2ac\right)^2=\left(a^2-b^2+c^2-2ac\right)\left(a^2-b^2+c^2+2ac\right)\)
\(a^4+b^4+c^4-2a^2b^2-2b^2c^2-2a^2c^2\)
\(=\left(a^4-2a^2b^2+b^4\right)+2\left(a^2-b^2\right)c^2+c^4-4a^2c^2\)
\(=\left(a^2-b^2+c^2\right)^2-\left(2ac\right)^2\)
\(=\left(a^2-2ac+c^2-b^2\right)\left(a^2+2ac+c^2-b^2\right)\)
\(=\left(a-c-b\right)\left(a-c+b\right)\left(a+c-b\right)\left(a+c+b\right)\)
\(a\left(b^2+c^2\right)+b\left(a^2+c^2\right)+c\left(a^2+b^2\right)-2abc-a^3-b^3-c^3\)
\(=c\left(a-b\right)^2+\left[ab^2+ac^2+a^2b+bc^2-a^3-b^3-c^3\right]\)
\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)+ab^2+a^2b-a^3-b^3\)
\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)-\left(a^3-a^2b\right)+\left(ab^2-b^3\right)\)
\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)-a^2\left(a-b\right)+b^2\left(a-b\right)\)
\(=c\left(a-b\right)^2+c^2\left(a+b-c\right)-\left(a+b\right)\left(a-b\right)^2\)
\(=-\left(a-b\right)^2\left(a+b-c\right)+c^2\left(a+b-c\right)\)
\(=\left(a+b-c\right)\left(a-b+c\right)\left(-a+b+c\right)\)
ax - bx - a² + 2ab - b²
= (ax - bx) - (a² - 2ab + b²)
= x(a - b) - (a - b)²
= (a - b)(x - a + b)
\(a^2-b^2-2x\left(a-b\right)=\left(a-b\right)\left(a+b\right)-2x\left(a-b\right)=\left(a-b\right)\left(a+b-2x\right)\)
\(a^2-b^2-2x\left(a-b\right)\)
\(=\left(a-b\right)\left(a+b\right)-2x\left(a-b\right)\)
\(=\left(a-b\right)\left(a+b-2x\right)\)
\(=\left(b^2+c^2+2bc-a^2\right)\left(b^2+c^2-2bc-a^2\right)\)
\(=\left(b+c-a\right)\left(b+c+a\right)\left(b-c-a\right)\left(b-c+a\right)\)
a2 – b2 – 4a + 4
= a2 – 4a + 4 – b2
= (a – 2)2 – b2
= (a – 2 + b)(a – 2 – b)
= (a + b – 2)(a – b – 2)
Lời giải:
$x^2-y^2+a^2-b^2+2ax+2by=(x^2+a^2+2ax)-(y^2+b^2-2by)$
$=(x+a)^2-(y-b)^2=(x+a-y+b)(x+a+y-b)$
\(a^2-b^2-ac+bc=\left(a^2-b^2\right)-\left(ac-bc\right)=\left(a-b\right)\left(a+b\right)-c\left(a-b\right)=\left(a-b\right)\left(a+b-c\right)\)